Uji Galur Dan Varietas Tanaman Cabai terhadap Serangan Hama Lalat Buah (Bactrocera dorsalis Complex) di Dusun Sandan, Desa Bangli, Kecamatan Baturiti, Kabupaten Tabanan - NI MADE DWI ANTARI; I KETUT SUMIARTHA; NI NENGAH DARMIATI; I PUTU SUDIARTA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2014)
ABSTRACT Cultivars and Varieties Test of Chili Plants Against Fruit Flies (Bactrocera dorsalis Complex) at Sandan, Bangli Village, Baturiti District Tabanan Regency The experiment was conducted at Sandan, Bangli Village, Baturiti District Tabanan Regency, in February to June 2012. In this study all cultivars and varieties of long chilies were cultivated with treatments such as in the field. The purpose of this study was to determine the cultivars and varieties of chilies plants that resistant to fruit fly (Batrocera dorsalis complex), to determine the number of branches and plant height were associated with yields as well as to determine the characteristics that influence the percentage of fruit fly infestation on fruit and results obtained for each long chilies plants. This study used a randomized block design (RBD) with three replications. The result revealed that the higest fruit flies infestation on AVPP 1004 while the lowest fruit flies infestations on local Kencana in 114 days after transplanting. High and low levels of infestation influenced by the environmental factor and characteristics of the fruit. The fruit characteristic of AVPP 1004 have thicker flesh than the local Kencana varieties, it can be seen from the fruit weight of cultivar AVPP 1004 (20.46 g) and local Kencana varieties (3.70 g). Keyword: Bactrocera dorsalis complex, long chili cultivars, the level of infestation.